Witchcraft of Saluang Sirompak: Music of Broken Hearts in the Taeh Baruah Minangkabau Community - Nil Ikhwan (International Journal of Visual and Performing Arts, 2020)
Saluang Sirompak is a type of music that has spiritual power in Taeh Baruah, Payakumbuh District, Lima Puluh Koto Regency, Minangkabau, West Sumatra. Saluang Sirompak is a show aimed at witchcraft, a woman who has insulted a man who wants to propose to her. This witchcraft activity is known as Basirompak. The problem that was revealed was how the music of Saluang Sirompak affected women's mental disorders. The ethnographic method was used in this study - the data were obtained through observation and interviews with actors or musicians Saluang Sirompak. The analysis was carried out by paying attention to the function of music and the organology of the musical instruments as a power-producing tone that can affect mental disorders for women who are the target victims. The conclusion that can be drawn is that witchcraft in Basirompak activities can distinguish what is right and what is wrong; If the women were not mistaken, they would not be victims of Basirompak's activities.